Evaluation of electrocardiographic parameters in patients with diabetes insipidus - KEPEZ, ALPER (SPRINGER WIEN, 2015)
Background There is limited data regarding the effect of altered serum osmolality on cardiac electrical activity. The aim of the present study is to evaluate the electrocardiographic (ECG) effects of diabetes insipidus (DI) and any related hyperosmolality in a population of young patients with DI and without any known cardiovascular disease or risk factors. Methods Twelve-lead ECG's of 44 consecutive untreated young male patients (age: 21.8 +/- 2.9 years) who had been referred to endocrinology clinic and diagnosed as DI based on water deprivation test were retrospectively evaluated. A total of 30 age-matched (21.9 +/- 2.4 years) healthy males were selected as control group and ECG's of these controls were obtained for comparison with ECG's of DI patients. All ECG parameters were measured and compared. Results Duration of QRS complex was significantly shorter in patients with DI compared with controls (85.2 +/- 12.0 vs. 94.0 +/- 10.6 ms, p: 0.001). P wave dispersion (PWD) of patients with DI was significantly higher compared with controls (31.9 +/- 9.9 vs. 26.5 +/- 10.6 ms, p: 0.03) and it was significantly correlated with serum osmolality and serum sodium level (r = -aEuro parts per thousand 0.36, p: 0.02 and r: -aEuro parts per thousand 0.35, p: 0.02, respectively). Conclusions DI patients without any cardiovascular disease or risk factors displayed significantly shorter QRS duration and increased p wave dispersion compared with controls.
Keywords: Diabetes insipidus; Electrocardiography; Osmolality; Electrolytes; Sodium; QRS duration; MUSCLE; POTASSIUM; CURRENTS